2019
DOI: 10.3390/app9040779
|View full text |Cite
|
Sign up to set email alerts
|

Design and Characterization of Electrically Conductive Structures Additively Manufactured by Material Extrusion

Abstract: Multi-material additive manufacturing offers new design freedom for functional integration and opens new possibilities in innovative part design, for instance, a local integration of electrically conductive structures or heat radiant surfaces. Detailed experimental investigations on materials with three different fillers (carbon black (CB), carbon nanotubes (CNT) and nano copper wires) were conducted to identify process-specific influencing factors on electrical conductivity and resistive heating. In this rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(106 citation statements)
references
References 26 publications
5
73
0
Order By: Relevance
“…However, with FFF printing, defects, By using printers with dual or multiple extrusion nozzles, multicolored or multiple material parts can be produced. Simultaneous 3D printing of multiple materials enables integration of different properties (e.g., flexibility, folding, deployment, shape memory, and electric conductivity) into intricate products in a single manufacturing process [15][16][17][18]. Additionally, a wide range of polymers used for FFF nowadays can be recycled, and the nonmelted material (metal and polymer) from different AM processes can be reused [3,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…However, with FFF printing, defects, By using printers with dual or multiple extrusion nozzles, multicolored or multiple material parts can be produced. Simultaneous 3D printing of multiple materials enables integration of different properties (e.g., flexibility, folding, deployment, shape memory, and electric conductivity) into intricate products in a single manufacturing process [15][16][17][18]. Additionally, a wide range of polymers used for FFF nowadays can be recycled, and the nonmelted material (metal and polymer) from different AM processes can be reused [3,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…In particular taking into consideration the Tg of PLA matrix, a specific approach to compensate the temperature effect on resistivity of PLA conductive sample in the range 20-50 • C has been discussed (Daniel et al, 2018;Coleman et al, 2019). The crucial effect of heating and distorsion in PLA conductive composites after voltage application has been recently detailed in dependence on the various process factors (extrusion and additive manufacturing); the authors compared the role of conductive filler (carbon black, carbon nanotubes, and nano copper wires) on resistivity in view of application for thermal sensors and piezo-resistive sensors (Watschke et al, 2019). Commercial graphene-PLA filaments with resistivity of 0.6 .cm, are designed to be used for room-temperature operation, due to the low softening temperature (50 • C), and for low-voltage and low-current only (lower than 12 volts and 100 mA, respectively) 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Combining multi-material fused-filament fabrication (FFF) and functional composite materials enables the fabrication of an object with embedded functional elements (sensorics [1], actuation [2], heating [3], and energy storage [4], etc.) in a single-step printing process.…”
Section: Introductionmentioning
confidence: 99%
“…For the Electrifi material [24] used in this work, the manufacturer specifies the right process parameters to attain a higher conductivity of the printed structure, or in other words, to minimize the degradation of the conductive network in the material during the extrusion process. Watschke et al [3] researched the effects of raster angle, print speed, flow rate, and extrusion temperature on the conductivity and heat-radiation capacity for four different filaments, including the Electrifi. Hampel et al [25] identified the optimal process parameters (layer height, printing speed, nozzle temperature, and cooling) and derived a conductive model for the electrical circuit's fabrication.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation